Forecasting Aspects of the Russian and Worldwide Markets of Forest Products - APSALYAMOVA, Saida Olegovna; KHASHIR, Bella Olegovna; KHUAZHEV, Oleg Zakireevich (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The purpose of the present study consists in carrying out analysis of the current situation and development prospects of Russian and global forest products’ markets. In the Russian Federation and the CIS countries, due to the depreciation of the ruble and other national currencies, export of all major types of forest products reached the highest level that in many cases allowed compensating for the lack of domestic demand, and stimulated production growth. Economic changes, having implications for the forest sector, were caused due to the fact that global economic growth in 2015 slowed down resulting from the reduction in performance indicators in regions with unstable emerging economies. At that, the process of rapprochement of the level of income in regions that have long been developed in terms of the forest industry, continued, albeit at a slower pace than before the global financial crisis. However, the negative trends observed in the Russian Federation and the CIS at the end of 2014, on the contrary, have amplified, while slow growth of economy was replaced by a clear decline in the production. Based on the use of analysis, synthesis, and generalization of expert materials on the state of the Russian and worldwide markets for forest products, as well as the theoretical forecasting to determine the future of the forest products’ markets, conclusions were drawn about the ambiguity of the forest products’ production and consumption in the long run. The increase in demand for timber in the global scale is influenced by demographic changes, economic growth of states, regional changes, environmental policies of states and adopted regulations, as well as a contemporary energy policy. In the conclusion of the study, policy measures of the state and the private sector were proposed aimed at improving the efficiency of foreign trade activities of the Russian Federation in the forestry sector.